An Unusual Association of Odontomas with Primary Teeth - Yıldırım-Öz, Gülsün; Tosun, Gül; Kızıloğlu, Dilek; Durmuş, Ercan; Şener, Yağmur (European Journal of Dentistry, 2007)
Odontomas generally appear as small, solitary or multiple radio-opaque lesions found on routine radiographic examinations. Traditionally, odontomas have been classified as benign odontogenic tumors and are subdivided into complex or compound odontomas morphologically. Compound odontomas commonly occur in the incisor-canine region of the maxilla and complex odontomas are frequently located in the premolar and molar region of both jaws. Occasionally, odontoma may cause disturbances in the eruption of teeth such as impaction, delay eruption or retention of primary teeth. In general, odontomas occur more often in the permanent dentition and are very rarely associated with the primary teeth. In this report; two cases of compound odontoma associated with primary teeth is presented. (Eur J Dent 2007;1:45-49)
Keywords: Odontoma; Primary teeth